2022
DOI: 10.1002/mnfr.202200171
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Xylo‐Oligosaccharides (XOS) Ameliorates Diarrhea Symptoms in Mice via Intestinal Barrier Improvement and Gut Microbiota Modulation

Abstract: Xylo‐oligosaccharides (XOS) has a bidirectional regulatory effect, and can be fermented by gut microbiota. This study aims to investigate how XOS alleviates Folium Sennae extracts induced diarrhea in mice. KM mice are given different concentration XOS for 3 weeks, and then Folium Sennae (Senna alexandrina Mill) extracts solutions (0.8 g mL−1) are given to establish diarrhea model. The results show that doses of XOS at 0.25 mg g−1 BW day−1 and higher could alleviate diarrhea symptoms by decreasing the disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Several studies have reported the impact of dietary XOS supplementation on improving growth performance in chickens [ 14 , 17 , 40 – 44 ]. This positive effect has been associated with their capacity to modulate the gut microbiota, regulate the immune function, and enhance gut health [ 16 , 19 , 45 , 46 ]. In addition, AX supplementation have also been reported in the literature [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the impact of dietary XOS supplementation on improving growth performance in chickens [ 14 , 17 , 40 – 44 ]. This positive effect has been associated with their capacity to modulate the gut microbiota, regulate the immune function, and enhance gut health [ 16 , 19 , 45 , 46 ]. In addition, AX supplementation have also been reported in the literature [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 XOS dietary supplementation has been demonstrated in numerous published research studies to change the gut microbiota's composition by enhancing the abundance of Bifidobacterium and Lactobacillus . 24,25 XOSs demonstrated an anti-constipation effect by increasing fecal moisture and the number of Bifidobacterium species. 26 However, the precise mechanisms underpinning XOSs from corn cobs to treat constipation effectively are still entirely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that XOS improved the growth performance, immune function, and antioxidant activity of weaned piglets (Pang et al, 2021b ). In addition, XOS contributed to maintaining the integrity of the intestinal barrier (Tong et al, 2022 ), antibacterial activity (Pang et al, 2021a ), and anti-inflammatory properties (Ding et al, 2018 ). The research showed that xylo-oligosaccharides of 100 g/t could significantly increase the content of short-chain fatty acids (SCFA) in piglets (Su et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%